1989
DOI: 10.3186/jjphytopath.55.579
|View full text |Cite
|
Sign up to set email alerts
|

Two satellite RNAs found in cucumber mosaic virus strain Y.

Abstract: Two satellite RNAs were found in cucumber mosaic virus strain Y (CMV-Y)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

1991
1991
1995
1995

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
1
1
Order By: Relevance
“…sat-RNA, but rather to be due to a preference for a particular sat-RNA. In a study with the Y sat-RNA, one sat-RNA variant, which was apparently a low-level contaminant, was also shown to be preferentially amplified over another, upon repeated passage (Nakashima and Ehara 1989). These results contrast with a recent study in…”
Section: Resultscontrasting
confidence: 56%
“…sat-RNA, but rather to be due to a preference for a particular sat-RNA. In a study with the Y sat-RNA, one sat-RNA variant, which was apparently a low-level contaminant, was also shown to be preferentially amplified over another, upon repeated passage (Nakashima and Ehara 1989). These results contrast with a recent study in…”
Section: Resultscontrasting
confidence: 56%
“…However, the satellite sequences could exist in the plant genome in fragments, which, under appropriate conditions are brought together. Although many laboratories have reported the "spontaneous" appearance of satellites in experimental plants (25,51,57,99,115,123,147,155,157,164,183,195,197), most of these could be accounted for either by very low levels of satellites already existing in virus isolates, which are amplified under the appropriate conditions (i.e., experimental conditions), or by contamination of experimental plants with satellite. In one study of CMV satellite RNAs, the satellite RNA molecules were shown to be stable on tobacco plants for 25 days in the absence of helper virus (88).…”
Section: Originsmentioning
confidence: 99%